Preliminary Results of MRI-guided Brachytherapy in Cervical Carcinoma: The Chiangmai University Experience - Tharavichitkul E. (2014)
This study was performed to evaluate the feasibility of magnetic resonance imaging (MRI) in the treatment planning of image-guided brachytherapy for cervical carcinoma. Seventeen consecutive patients with locally advanced cervical cancer were enrolled in the study. Fifteen patients could be evaluated. When comparing the tumor at diagnosis (GTV-Dx) and the tumor at the first brachytherapy (GTV-BT), 11 of 15 patients showed a tumor regression of more than 80% while only four patients had less than 80% tumor regression. The mean D90 of HR-CTV and the calculated D2cc of the bladder, rectum, and sigmoid were 99.2 ± 11 Gy, 87.7 ± 5.7 Gy, 68.4 ± 5.4 Gy and 70.3 ± 6.8 Gy, respectively. No grade 3-4 acute toxicity was observed. The MRI can be a valuable tool for evaluating tumor response after external beam radiotherapy (EBRT) and is very helpful for prognosis prediction by residual GTV evaluation. Furthermore, MRI-guided brachytherapy allowed us to optimize the dose for both the target volumes and the OARs.